2018
DOI: 10.1080/20008198.2018.1518199
|View full text |Cite
|
Sign up to set email alerts
|

The study of service dogs for veterans with Post-Traumatic Stress Disorder: a scoping literature review

Abstract: The fourth author in this published Review Article is incorrectly displayed. The correct name of the fourth author is Bas Rodenburg. The original version has been corrected to reflect this change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Partnership with a psychiatric assistance dog, a type of assistance dog trained to assist individuals with mental health diagnoses including PTSD, has become increasingly popular among veterans with PTSD [ 5 , 6 ]. Yet even with this growing popularity, there remains a need for empirical data to evaluate their use [ 7 , 8 ]. The purpose of this literature review is to systematically identify and evaluate existing evidence on the placement of psychiatric assistance dogs for service members or veterans with PTSD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Partnership with a psychiatric assistance dog, a type of assistance dog trained to assist individuals with mental health diagnoses including PTSD, has become increasingly popular among veterans with PTSD [ 5 , 6 ]. Yet even with this growing popularity, there remains a need for empirical data to evaluate their use [ 7 , 8 ]. The purpose of this literature review is to systematically identify and evaluate existing evidence on the placement of psychiatric assistance dogs for service members or veterans with PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this $16M study, summarized in the form of a VA Report published in early 2021, are among a growing body of literature exploring the impact of these placements on health outcomes for military service members and veterans with PTSD [ 18 ]. To date, there has only been one review exclusively focused on assistance dogs for PTSD [ 8 ]. This review collated the literature on assistance dog placement for veterans with PTSD and found 19 articles on the topic.…”
Section: Introductionmentioning
confidence: 99%
“…The interpersonal interactions and relationships, general tasks and demands, mobility, self-care, domestic life, major life areas, and community, social and civic life domains were all mapped across studies, irrespective of diagnosis. This adds to current understanding of assistance dogs as many previous reviews only investigated participants with a specific disability (Catala et al, 2018;van Houtert et al, 2018;Winkle et al, 2012). The broad range of participation outcomes highlights the flexibility of the assistance dog partnership that is important as individuals have diverse participation goals and priorities irrespective of diagnosis (Magasi et al, 2009;Martin Ginis et al, 2017).…”
Section: Participation Outcomes Impacted By Assistance Dogsmentioning
confidence: 93%
“…Sachs-Ericsson et al (2002) did consider participation outcomes, but the review only included assistance dogs for persons with hearing or physical impairments. More recent reviews considered participation outcomes but were limited to a single disability group (van Houtert et al, 2018;Winkle et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Military veterans and police officers are known to suffer from mental health issues associated with their profession (Van Houtert et al 2018). An app (Backup Buddy) was developed to help and support front-line police officers in numerous UK police forces to identify the most commonly reported conditions and to provide them with advice and support as to what users could use to help themselves or colleagues.…”
mentioning
confidence: 99%